Faktor-Faktor yang Berhubungan dengan Pemberian MP-ASI Dini di Wilayah Kerja Puskesmas Tiworo Kepulauan Kabupaten Muna Barat - Yunadi, Marma; Ihsan M, Habib; Abadi, Ellyani (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2022)
Complementary food of breast milk which fed earlier on infants causes health problems. There will be short-term or long-term effects. The data from Tiworo Kepulauan health center was 93% infants have been fed early complementary food of breast milk. This study aimed to identify factors related to feeding early complementary food of breast milk. It’s a quantitative used cross sectional study. 110 mothers who have infants aged 6-12 months at Tiworo Kepulauan health center agreed to participate, and 52 people of them who were chosen by using Proportionate Stratified Random Sampling fully completed the questionnaires. The data was analyzed by using Fisher Exact test. Mother’s job was obtained with p value 0.78, mothers’ knowledge was obtained with p value 0.000, the quantity of breast milk with p value 0.78, social culture with p value 0.000, and family support with p value 0.000. Therefore, it concluded that mother’s knowledge, social culture, and family support were significantly correlated with feeding early complementary food of breast milk. Mother’s job and quantity of breast milk were not correlated with feeding early complementary food of breast milk at working area of Kepulauan Tiworo health center, district of Muna Barat. This study suggested for those health agencies to do health promotion regularly, such as conducting trainings about exclusive breast milk and recommending the infants should not be fed complementary food of breast milk before 6 months of age, mothers also need to improve their knowledge by looking various information related to complementary food of breast milk.